Stationary distribution of a process of random semi-Markov evolution with delaying screens in the case of balance - Pogorui A. О. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We determine a stationary measure for a process defined by a differential equation with phase space on the segment [V_0 , V_1] and constant values of a vector field that depend on a controlling semi-Markov process with finite set of states.